China's Challenges in Moving towards a High-income Economy - Song, Ligang; Zhou, Yixiao (China Update Series, 2021)
With its per capita income surpassing US$10,000, China has now drawn up ambitious plans to further lift its income to the level of developed countries. Yet various constraints need to be overcome if China is to build on the achievements of the last 40 years and further boost its growth potential. Besides these constraints, the year 2020 saw human societies hit heavily by the COVID-19 pandemic and the global economy caught off guard and dipped into recessions caused by lockdown measures for controlling the spread of the pandemic. Nations around the world have experienced grave loss of human life and lockdown measures have knocked economies from their normal growth trajectories. Even as the pandemic continues to unfold, all signs point to China as being the first major economy to have emerged out of the crisis. But many questions remain. Has the Chinese economy emerged from the pandemic crisis relatively unscathed? What are the long-term prospects for its economy? This year's Update book, China's Challenges in Moving towards a High-income Economy, explores the challenges faced by the Chinese economy in the transition towards a high-income economy, including agricultural development, finance and fiscal system reform, RMB internationalisation, trends in urbanisation, as well as topics related to innovation, corporate sector development and market competition. China's growth experience has been full of exciting changes and important lessons for reform and structural changes, and this year's China Update is again the way to gain insights into these.